Rola cła w rozwoju gospodarczym kraju ze szczególnym uwzględnieniem czasów współczesnych - Machalica-Drozdek, Katarzyna (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2019)
The institution of customs duty is one of the oldest public levies collected when goods cross the customs border of a settlement or state. It has evolved over the centuries, which at the turn of the twentieth and twenty-first century resulted in reduced customs burden in trade with third countries. As a consequence, it is much harder for entities importing goods to pay taxes on imported goods than to pay customs duties. At present, European Union customs policy is aiming at facilitating foreign trade, which is embodied in the implementation of information instruments that are supposed to accelerate customs clearance
Keywords: customs; public levy; economic growth; European Union